Analysis of Compensation, Competence, Workload, Work Motivation, and Self-Efficacy on the Performance of Pharmacists in Banyumas Regency - Retno Fitri Widiastuti; Eko Haryanto; Wida Purwidianti; Amir Amir (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of compensation, competence, workload, work motivation, and self-efficacy on the performance of pharmacists working in pharmacies in Banyumas Regency. The population of this study was pharmacists working in pharmacies in Banyumas Regency, with a sample of 100 respondents. This study used a quantitative approach with convenience sampling. Data analysis was performed using SEM PLS. The results showed that compensation, competence, work motivation, and self-efficacy had a positive and significant effect on pharmacists' performance, unlike workload, which had a positive but insignificant effect on pharmacists' performance. These findings indicate that internal factors such as motivation and self-efficacy have a greater influence on performance than external factors such as workload. This study contributes to the formulation of human resource management strategies in pharmacies, particularly in strengthening competencies, providing fair compensation, and increasing the motivation and self-efficacy of pharmacists to improve the quality of pharmaceutical services.